Introducing environmental thresholds into water withdrawal management of mountain streams in the Kura River Basin, Azerbaijan - Abbasov, R.K.; Smakhtin, Vladimir U. (Informa UK Limited, 2009)
The study aims to set and implement environmentally relevant limits for the exploitation of mountain streams in the Kura River basin of Azerbaijan. Such streams represent the preferred spawning grounds for valuable sturgeon of the Caspian Sea, but experience continuously increasing exploitation in the form of water withdrawals for industry and irrigation. Since no detailed environmental flow assessments have been conducted on any of the Kura basin streams, an interim approach is suggested based on minimum flow, referred to as "base environmental minimum?. The latter may be estimated from the unregulated parts of observed or simulated daily flow records. Environmental flow requirements for individual months of an individual year may be calculated using correction factors related to monthly rainfall. Simple relationships are suggested for base environmental flow estimation at ungauged sites, and the implications of river pollution for monthly environmental requirements are examined. Further, definition of environmentally critical periods in a stream is proposed based on a ratio of observed to "environmental? flow as an indicator of environmental stress. It is illustrated that the conjunctive use of several closely located streams for water supply may significantly reduce the duration of, or completely eliminate, environmentally critical periods. The idea of environmentally acceptable areal water withdrawal is formulated, so that the overall approach may be applied for environmentally sustainable water withdrawal management in other small streams.